Statistical Distributions of Dayside ECH Waves Observed by MMS - Yuequn Lou; Xudong Gu; Danny Summers; Binbin Ni; Kaijun Liu; Song Fu; Zheng Xiang; Zhengyang Zou; Xing Cao; Wenxun Zhang; He Huang; Ying He (Geophysical Research Letters)
Abstract Strong electrostatic electron cyclotron harmonic (ECH) waves on the dayside magnetosphere have been reported based on observations of the Magnetospheric Multiscale (MMS) spacecraft. In this study, we analyze high‐quality wave data from the four MMS satellites between 1 September 2015 and 30 August 2018 to investigate the statistical properties of dayside ECH emissions. The results show that dayside ECH waves are preferentially observed on the prenoon side in the outer magnetosphere (L = 8–12), with average wave amplitude Ew > 0.1 mV/m. In addition, besides the typical near‐equatorial (|MLAT| ≤ 15°) region, dayside ECH waves exhibit moderate occurrence rate and wave amplitude in higher latitudinal regions (i.e., 15 < |MLAT| ≤ 40°), possibly due to the off‐equatorial geomagnetic field minimum. Our reported double peaks of dayside ECH wave occurrence zone and considerable occurrence rates of prenoonside ECH waves suggest that dayside ECH waves can be a potentially important contributor to the formation of dayside diffuse aurora.